2012
DOI: 10.1177/1088357612462060
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Individuals With Autism in a State Facility for Adolescents Adjudicated as Sexual Offenders

Abstract: Using the criteria established by the Commonwealth of Pennsylvania, the assessment procedures for establishing an autism spectrum disorder (ASD) in a previously undiagnosed adjudicated group is detailed. We examined 37 male adolescents adjudicated delinquent for sexual offenses who were sentenced to treatment. Ultimately, 22 (60%) were found to meet the diagnostic criteria for an ASD. All had intelligence quotients in the average range. For the offenders with ASD, we recommend modifying traditional treatment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 24 publications
0
17
0
2
Order By: Relevance
“…This finding was also observed in our previous studies after MSC transplantation to BTBR mice [ 5 ]. Considering the growing recognition that some adolescents and young adults with ASD may exhibit inappropriate sexual behaviors [ 22 , 23 ], the fact that MSC-exo treatment also does not enhance sexual arousal is an advantage. As compared, the C57BL MSC-exo group did not present behavioral changes in their ultrasonic vocalizations and social interactions toward both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was also observed in our previous studies after MSC transplantation to BTBR mice [ 5 ]. Considering the growing recognition that some adolescents and young adults with ASD may exhibit inappropriate sexual behaviors [ 22 , 23 ], the fact that MSC-exo treatment also does not enhance sexual arousal is an advantage. As compared, the C57BL MSC-exo group did not present behavioral changes in their ultrasonic vocalizations and social interactions toward both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is some evidence that individuals with ASD are at increased risk for problematic sexual behaviors that can include undesired touching, public masturbation and other illegal activity [1]. Few investigations of problem sexual behavior in ASD exist, but one related study found that 60% of a sample of 37 male adolescents adjudicated for sexual offenses and sentenced to treatment met diagnostic criteria for ASD [38]. Further, even when problem behaviors are not illegal, inappropriate sexual behaviors can limit employment and inclusion opportunities for individuals with ASD [20].…”
Section: Positive and Respectful Approach To Sexuality And Sexual Relmentioning
confidence: 99%
“…However, establishing the state factors for clients with comorbid Level 2/3 autism and an ID appears to be an outstanding area in the ITSO. For example, whilst there is ample evidence that clients with autism and ID may experience increased emotional and behavioural regulation difficulties (Sutton et al, 2013) it is unclear how the factors 'need for intimacy' due to 'loneliness, inadequacy and low self-esteem' may apply to a person with autism where there is a high likelihood of them experiencing mind-blindness and alexithymia (Brewer, Cook and Bird, 2016).…”
Section: )mentioning
confidence: 99%